The Students, the Local and the Foreign: Drama of Identity and Language in Mongolian-English Bilingual Schools - Flora Komlosi-Ferdinand (National Research University Higher School of Economics, 2020)
Education in bilingual schools aims to equip learners with balanced bilingualism, increased (bi)cultural capital and a global mindset. Nevertheless, in a growing number of countries only local children attend such institutions, where foreign teachers are the almost exclusive manifestations of 'globalness'. Dynamics among foreign and local teachers and students shape learners' attitudes, their learning outcome and identity formation to an unexpected degree. This often produces unhealthy perceptions and behaviour towards among the groups and the taught languages as well, eventually students not benefiting from bilingual education to the expected extent, if at all. One of the oldest and one of the newest bilingual schools in Ulaanbaatar, Mongolia, were observed for this study. Local and foreign teachers of these schools contributed with their experiences in the form of unstructured interviews, while classroom observations shed light on students' attitudes. The findings reveal that students respect local educators more and display more respect and discipline with them. However, pupils are usually more emotionally attached to foreign teachers, confiding in them and seeking their company on a daily basis, yet refusing to be disciplined and to study for their classes. Students' unbalanced attitudes towards the two groups of teachers generated unease between the educators as well. This paradox created an unhealthy milieu in the schools and discouraged the development of a healthy perspective on (foreign) languages and identity. Teachers' attitudes further compromised learners' behaviour, as local educators stressed nationalism, while foreigners pressed towards the development of a more global mentality. Unfortunately, as none of the institutions had any policies to address this dilemma, eventually students developed behaviours contrary to the intended by the schools.